Summer recurrent papular dermatitis of childhood. - Milano, A. (European Journal of Pediatric Dermatology, 2018)
The current study examines the relationship between summer recurrent papular dermatitis of childhhod (SRPDC) and the most frequent constitutional dermatitis, especially atopic dermatitis. Starting from the examination of a complex case and personal data in 39 cases of SRPDC, the authors believe that SRPDC is a separate disease, but able to be influenced and to influence the most common constitutional infant dermatitis as atopic dermatitis and psoriasis.